Bupivacaine/Butorphanol/Epinephrine for Epidural Anesthesia in Obstetrics: Maternal and Neonatal Effects. Issue 5 (September 1989) - Abboud, T. K.; Reyes, A.; Steffens, Z.; Afrasiabi, A.; D'onofrio, L.; Davidson, J.; Zhu, J.; Khoo, N.; Paul, R.; Mantilla, M.; Mosaad, P.
Abstract : The effects of epidural bupivacaine/butorphanol with and without 1:300, 000 epinephrine on maternal analgesia, uterine activity, progress of labor, fetal heart rate, maternal blood pressure, newborn Apgar scores, neonatal acid base status and the neurologic and adaptive capacity scores (NACS) were compared in 33 parturients during labor and delivery. Patients in Group I (n = 17) received 0.25% bupivacaine plus 1 mg butorphanol plus 1:300, 000 epinephrine, and those in Group II (n = 16) received the same agents without the epinephrine. Addition of epinephrine to bupivacaine/butorphanol did not have any adverse effects on uterine activity, duration of first or second stages of labor or fetal heart rate parameters. The incidence of maternal hypotensive episodes did not differ significantly between the two groups of patients. Apgar scores, neonatal acid base status and the NACS were equally good and did not differ significantly between the two groups. Duration of analgesia was significantly longer in Group I as compared to Group II patients (177.5 ± 11 versus 131.8 ± 10 minutes, p < 0.01). It is concluded that addition of epinephrine 1:300, 000 to bupivacaine/butorphanol during epidural anesthesia in the normal parturient has no adverse effects on the mother, fetus or neonate or on the progress of labor and it significantly prolongs the duration of analgesia.